Upaya Peningkatan Penjualan melalui Kegiatan Pemasaran (Marketplace) di Era New Normal - Muhammad Takrim; Hanif Aulawi; Apriani Simatupang; Yulia Indriyani (Jurnal Pemberdayaan Umat, 2022)
Purpose: This activity aims to provide training to MSME actors to increase sales through marketplaces in the era of the covid-19 pandemic. Method: This activity assists with registering sales through marketplaces, help share product photos, manage sales and evaluate. Results: This dedication output increases knowledge of understanding the types of marketplaces, understanding of sales strategies, understanding of self-motivation in dealing with Covid-19 and understanding of good sales in carrying out sales during current conditions. Conclusions: In this activity, there were 63 participants attending Zoom and 80% participants understood this training concept. The remaining 20% of new MSME entrepreneurs still did not understand it because they were the beginner in online business.